Analysis of Failure in The Fire System Alarm on The Ship KL.02 Sultan Hasanuddin - Tjahjanto, Rachmat; Wira Perdana, Fadjrin (Mutiara: Multidiciplinary Scientifict Journal, 2024)
International Maritime Organization (IMO) has set regulations governing the installation of fire alarm systems on ships. The basic principle of the control system is to control the system output by comparing the actual output with the desired output. This study aims to determine the causes of false alarms on the fire alarm system on ships and to describe recommendations and solutions for failures in the fire alarm system on ships. This type of research uses a mix of methods by utilizing primary and secondary data. The data is processed by quantitative analysis and qualitative research. The results of this study indicate that the cause of the False Alarm on the Fire Alarm System is caused by the MFCA, Smoke Detector, and Cable Installation. The case that occurred in KL. 02 Sultan Hasanuddin there is no correlation between false alarms on the Fire Alarm System. The Smoke Detector correlation data with the False Alarm Fire Alarm System shows that there is a correlation with the Pearson Correlation of 0.857 > 0.4973. This study concluded that improving the reliability of fire alarm systems can be achieved through better maintenance of smoke detectors and proper technical training for ship operators.